Análise, projeto e desenvolvimento de sistemas multiníveis híbridos - Rech, Cassiano (2005)
This Ph.D. Dissertation presents contributions to the study of hybrid multilevel systems, analyzing several issues that compose this system, such as: topological variations of the output inverter stage and input rectifier stage, design methodologies, modulation strategies and control system. This extensive analysis is carried out because these issues are closely related, so that a modification in any element can affect the overall system performance. Initially, due to the enormous flexibility and large complexity to design hybrid multilevel converters, this work proposes a unified analysis for these converters, which are composed of several series-connected cells with distinct voltage levels, modulation strategies, topologies and/or semiconductor technologies. This unified analysis includes a detailed comparative analysis among distinct topologies and a new generalized design methodology. Different configurations of hybrid converters are proposed from this new design methodology, depending on the specifications imposed to the multilevel system. Therefore, this work can be used as a valuable tool to define an adequate hybrid configuration for a specific application. After, this work also proposes a new arrangement to implement the isolated voltage sources of the series-connected cells that compose a hybrid multilevel inverter. This new arrangement is based on the multipulse connection of uncontrolled rectifiers processing distinct power levels, unlike conventional multipulse converters. A new design methodology for this input stage is proposed in this work, defining the phase shifts among the secondaries of the isolation transformer to eliminate dominant harmonics from the current drawn from the utility grid even when the active power levels processed by rectifiers are different. This work also investigates the impact of the hybrid multilevel modulation strategy on the harmonic contents of the output voltages and input currents. After to demonstrate the negative impact of the modulation strategy on the input harmonic performance for some operating points, this Ph.D. Dissertation proposes a new modulation strategy that makes possible, together with an asymmetrical multipulse connection of rectifiers, to eliminate undesired harmonics from the input current in any operating point without affecting the output harmonic performance. Beyond these issues, this work also includes a qualitative analysis about hybrid multilevel inverters operating as actuators in closed-loop systems, to motivate a discussion about this new subject. Finally, several experimental results are presented to demonstrate the practical feasibility of some proposals of this Ph.D. Dissertation.